Fracturing location optimization of floor coalbed methane wells with high water content in Hancheng Block - Wei WANG; Haifeng ZHAO; Dezhi WANG; Wang ZHANG; Liang JI; Hong JIANG (Meikuang Anquan)
In order to study the influence of fracturing location on the production of coalbed methane wells in floor with high water content, the 11# coal seam in Hancheng Block was taken as the research background, and Petrel integrated geological engineering software was used to simulate the influence law of three fracturing locations of roof, roof + coal seam and coal seam on the production of coalbed methane wells. The results show that when the coal reservoir is 1 m and 5 m away from the high aquifer, the three fracturing methods show the characteristics of low gas production, high water production and late gas occurrence time. When the distance from the aquifer increases to 10 m and 15 m, the variation range of water and gas production is small. Under the influence of floor high water content, the cumulative gas production of the three fracturing locations is from large to small: roof > coal seam + roof > coal seam; the coal seam, in which the roof fracturing has high peak daily gas, short gas emergence time and low water production, is less affected by high aquifer, and is more suitable for the fracturing reconstruction of coal bed gas wells with high water content in the floor. Three kinds of fracturing positions have been verified in Hancheng Mining Area, and the research results can provide guidance for the selection of fracturing location of floor coal seam with high water content.